GMP development and preclinical validation of CAR-T cells targeting a lytic EBV antigen for therapy of EBV-associated malignancies - Zhang, Xi; Wang, Tiaoxia; Zhu, Xiaona; Lu, Yong; Li, Mingpeng; Huang, Zhihong; Han, Deping; Zhang, Longzhen; Wu, Yang; Li, Liantao; Klawonn, Frank; Stripecke, Renata (Frontiers in Immunology, 2023)
Epstein-Barr virus (EBV) is a widely spread pathogen associated with lymphoproliferative diseases, B/ T/ NK cell lymphomas, nasopharyngeal carcinoma (NPC) and gastric carcinoma (GC). EBV lytic reactivations contribute to the genomic instability, inflammation and tumorigenesis of NPC, promoting cancer progression. Patients with NPC refractory to standard therapies show dismal survival. EBV gp350 is an envelope protein detectable in NPC specimens intracellularly and on the cell membrane of malignant cells, and is a potential viral antigen for T cell-directed immunotherapies. The potency of T cells engineered with a chimeric antigen receptor (CAR) targeting gp350 against EBV+ lymphoproliferative disease was previously shown. Here, we advanced towards preclinical and non-clinical developments of this virus-specific CAR-T cell immunotherapy against NPC. Different gp350CAR designs were inserted into a lentiviral vector (LV) backbone. A construct expressing the scFv 7A1-antigp350 incorporating the CD8 transmembrane and CD28.CD3ζ signaling domain (ZT002) was selected. High titer ZT002 (~1x108 TU/ml) was manufactured in HEK 293T/17 suspension cells in serum free media as large-scale production under good manufacturing practices (GMP). A LV multiplicity of infection (MOI) of 1 resulted in high frequencies of functional gp350CAR+ T cells (>70%) at a low (<2) vector copy numbers in the genome. ZT002 was therefore used to establish gp350CAR-T batch run production methods. GMP upscaling and validation of T cell transduction and expansion in several runs resulted in average 3x109 gp350CAR-T cells per batch. >80% CD3+gp350CAR-T cells bound to purified gp350 protein. In vitro cytotoxicity and cytokine secretion assays (IFN- and TNF-) confirmed the specificity of gp350CAR-T cells against gp350+ NPC, GC and lymphoma cell targets. Immunocompromised B-NDG mice (NOD.CB17-PrkdcscidIl2rgtm1/Bcgen) were challenged s.c. with a EBV+ NPC C666.1 cell line expressing gp350 and then treated with escalating doses of gp350CAR-T cells or with non-transduced T cells. gp350CAR-T cells promoted antitumor responses, bio-distributed in several tissues, infiltrated in tumors and rejected gp350+ tumor cells. These results support the use of gp350CAR-T cells generated with ZT002 as an Innovative New Drug to treat patients with solid and liquid EBV-associated malignancies.